First human experience of thermal arterial closure. Issue 1 (10th September 2013) - Davidson, Laura J.; Luna, Jorge; Virmani, Renu; Asscher, Jacqueline A.; Davidson, Charles J.
<x xml:space="preserve">Abstract</x> Objectives: This study was designed to evaluate the efficacy and safety of the CardioDex arterial closure device, which is a novel femoral artery closure device used following percutaneous cardiac catheterization. Background: Current devices utilized to achieve hemostasis of the femoral artery following percutaneous cardiac catheterization include collagen plug and suture mediated devices, but are associated with significant vascular complications. The CardioDex closure device utilizes thermal energy to cause collagen shrinking and swelling and thereby, achieve hemostasis. Methods: The device was evaluated in a prospective nonrandomized single‐center trial with patients undergoing 6F invasive cardiac procedures. Femoral artery puncture closure was performed immediately at completion of the procedure, followed by 3–4 minutes of manual compression. Time to hemostasis (TTH), time to ambulation (TTA), and short‐term clinical follow‐up data were collected. Results: A total of 34 patients including 21 diagnostic and 13 interventional cases were evaluated. The median TTH was 3 min in diagnostic and 4 min in interventional cases. TTH was independent of activated clotting time (ACT). The median TTA was 2.75 hr and 3.37 hr in diagnostic and interventional groups, respectively. There were no major adverse events identified at 1 week and 30 day follow up. Conclusions: This first in human clinical experience with the CardioDex closure device demonstrates that in the small cohort studied, it is safe and effective in diagnostic cardiac catheterization and also in interventional cases on mild anticoagulation (mean ACT = 188 sec). It has the advantage of leaving no foreign material in the body following use. © 2013 Wiley Periodicals, Inc.